Epilepsy: Knowledge and Attitudes of Primary School Teachers in the City of Bouake/Ivory Coast - AF Akani; HA Karidioula; KE Bony; A Gnazégbo; A-E Kouamé-Assouan; AC Tanoh; LL Diallo; A Sylla; YT Koffi (Journal of Neurological Research And Therapy, 2018)
We report the results of a two-month descriptive observational survey to assess the knowledge about epilepsy among primary school teachers in Bouake in Ivory Coast. This study included 310 teachers who were randomly chosen from three Primary School Inspections (PSI). Almost all the teachers who were included had shown inaccurate information about epilepsy. 46.45% of the respondents thought that epilepsy was contagious and 47.74% recommanded to avoid contacting with salivary secretions of the patient during seizure. For 16.45% of them, persons living with epilepsy (PWE) could be not married and 19.7% believed that PWE could not have children due to the risk of transmission. This study highlights the urgent need of awareness campaigns among primary school teachers.
Keywords: epilepsy- knowledge- africa - teachers.